Intregated Social Intelligence On The Development Character Education For Elementary School Student - Tri Joko Raharjo; Tri Suminar; Endah Wulansari; Yuli Sudargini; Rahmi Anekasari; harianingsih - (Indonesian Journal of Education Teaching and Learning (IJETL), 2022)
This study aims to create a model of integration of social intelligence in the character education curriculum for elementary school students. The variables contained in this study include situational awareness, presence, authenticity, clarity and empathy. The research method was carried out by respondent observation, data collection and analysis test using SEM. The results showed that all variables, both situational awareness, presence, authenticity, clarity and empathy had a positive influence on curriculum development. The integration of social intelligence is expected to shape the character of students who are more aware of other people and the surrounding environment